First-Pass Metabolism of Polyphenols from Selected Berries: A High-Throughput Bioanalytical Approach - Francisco J. Olivas-Aguirre; Sandra Mendoza; Emilio Alvarez-Parrilla; Gustavo A. Gonzalez-Aguilar; Monica A. Villegas-Ochoa; Jael T.J. Quintero-Vargas; Abraham Wall-Medrano (MDPI AG, 2020)
Small berries are rich in polyphenols whose first-pass metabolism may alter their ultimate physiological effects. The antioxidant capacity and polyphenol profile of three freeze-dried berries (blackberry, raspberry, Red Globe grape) were measured and their apparent permeability (Papp) and first-pass biotransformation were tracked with an ex vivo bioanalytical system [everted gut sac (rat) + three detection methods: spectrophotometry, HPLC-ESI-QTOF-MS, differential pulse voltammetry (DPV)]. Total polyphenol (ratio 0.07-0.14-1.0) and molecular diversity (anthocyanins > flavan-3-ols), antioxidant capacity (DPPH, FRAP), anodic current maxima and Papp (efflux> uptake) were in the following order: blackberry > raspberry > Red Globe grape. Epicatechin, pelargonidin & cyanin (all), callistephin (raspberry/blackberry), catechin (grape), cyanidin glycosides (blackberry) and their derived metabolites [quinic acid, epicatechin, cyanidin/malvidin glucosides, and chlorogenic/caffeic acids] were fruit-specific and concentration-dependent. Time-trend DPV kinetic data revealed concurrent epithelial permeability & biotransformation processes. Regular permeability and high-biotransformation of berry polyphenols suggest fruit-specific health effects apparently at the intestinal level.